Investment decision analysis on sustainable renewable energy policy: Literature review - Maria , Maria Magdalena Bate'e; Fachruddin, Khaira Amalia (MBR (Management and Business Review), 2023)
This paper discusses sustainable renewable energy policies. The method used in this paper is a descriptive method that collects data from various sources literature studies and previous research. The results of the literature review show that the development of renewable energy in the European Union has three clusters dividing the share of renewable energy and the degree of dependency on energy imports based on the country. In Pakistan, the government has been designing a renewable energy policy since 2006 to supply sustainable energy to all consumers. In Nigeria, the electricity crisis and the need to reduce greenhouse gases spurred the development of renewable energy. Denmark has moved to wind power sources by increasing the share of renewable energy in the domestic electricity supply. The government encourages local ownership in the renewable energy sector, and many neighborhoods are connected to district heating systems that use renewable energy such as biomass. Increased investment in renewable energy technology will aid in addressing global energy concerns and hastening the transition to a low-carbon economy.